FACTORS INFLUENCING THE INCIDENCE OF REFRACTORY EPILEPSY: A SCOPING REVIEW - Naufal; Desin Pambudi Sejahtera; Ishana Nafeeza Mukhtar; Atitya Fithri Khairani; Nur Chayati (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2026)
Background: Epilepsy affects around 50 million people worldwide, with an incidence of 100 cases per 100,000 people annually in developing countries where access to adequate treatment is limited. Refractory epilepsy occurs in 20-40% of cases of patients whose seizures remain uncontrolled despite 1-2 years of adequate anti-seizure medication (ASM) therapy with good adherence. This condition poses significant challenges for management. Objective: This scoping review aimed to systematically identify the factors associated with refractory epilepsy. Methods: A scoping review was conducted in accordance with the PRISMA-ScR guidelines and the PEO/PET framework. A systematic PubMed search identified studies published between 2020 and 2025 on factors influencing refractory epilepsy. Eligible studies underwent a three-phase screening process (title, abstract, and full-text review). Results: Twenty studies met the inclusion criteria, comprising seven review articles and thirteen clinical studies, most of which were observational. Recurrent associations between refractory epilepsy and several factors were identified, such as one large cohort of 5,794 patients reporting seizure onset within the first year of life to be the strongest predictor of refractory epilepsy, while another study showed that structural etiology increased the odds more than threefold (OR 3.47; 95% CI: 1.15-10.43). Psychiatric comorbidities, developmental delay, abnormal EEG or neuroimaging findings, and systemic contributors such as inflammation and metabolic disorders were also found to be commonly associated with refractory epilepsy. Conclusion: The most frequently reported factors for developing refractory epilepsy across studies were younger age at first seizure, structural etiology, and genetic factors.